Konsepsi Pemahaman Modern Kaum Mu’tazilah Dan Ajarannya - Ajmal Hadi Maulana; Aprilliani Dwi Andini; Putri Sheila Az Zahra; Ratna Primada Dewi; Shafira Nazibah; Muhammad Parhan (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Muslims always respond to each other's political problems that occurred during the Islamic civilization. This led to the emergence of understanding from several groups, one of which was the Mu'tazilah. Known as the concept of thinking that separates itself because it prioritizes reason over revelation, this unknowingly contributes to understanding. Be neutral, by not confirming one or another's thoughts. This research was conducted to determine the existence of the Mu'tazilah and their teachings as an old view that should not be lost. With the analytical methods from previous research, it is hoped that it can provide an expansion of knowledge in the treasures of Islamic civilization regarding all existing understandings in the 21st century. The results of this article recommend academics and research experts to continue and develop research as a reference and new knowledge for the progress of Islam from time to time.